2021
DOI: 10.3390/biom11081211
|View full text |Cite
|
Sign up to set email alerts
|

GNAi2/gip2-Regulated Transcriptome and Its Therapeutic Significance in Ovarian Cancer

Abstract: Increased expression of GNAi2, which encodes the α-subunit of G-protein i2, has been correlated with the late-stage progression of ovarian cancer. GNAi2, also referred to as the proto-oncogene gip2, transduces signals from lysophosphatidic acid (LPA)-activated LPA-receptors to oncogenic cellular responses in ovarian cancer cells. To identify the oncogenic program activated by gip2, we carried out micro-array-based transcriptomic and bioinformatic analyses using the ovarian cancer cell-line SKOV3, in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Integrins are involved in triggering FAK-Y397 phosphorylation, and a portion of FAK is located in the lipid raft/fossa structural domain where it interacts with FYN leading to elevated levels of FYN phosphorylation and elevated activity [ 63 ]. Microarray transcriptomic and bioinformatic analysis of ovarian cancer identified FYN as a key downstream target in the transcriptome of GNAi2/gip2 regulated tumor progression [ 64 ].…”
Section: Regulatory Mechanisms Of Fyn Expression and Activitymentioning
confidence: 99%
“…Integrins are involved in triggering FAK-Y397 phosphorylation, and a portion of FAK is located in the lipid raft/fossa structural domain where it interacts with FYN leading to elevated levels of FYN phosphorylation and elevated activity [ 63 ]. Microarray transcriptomic and bioinformatic analysis of ovarian cancer identified FYN as a key downstream target in the transcriptome of GNAi2/gip2 regulated tumor progression [ 64 ].…”
Section: Regulatory Mechanisms Of Fyn Expression and Activitymentioning
confidence: 99%
“…Lysophosphatidic acid (LPA), a lipid growth factor highly secreted in the ovarian tumor microenvironment [13], exerts several pro-tumorigenic activities such as (i) reprogramming toward a glycolytic shift that associates with the pheno-conversion of ovarian normal fibroblasts into cancer-associated fibroblasts (CAFs) [14] and with the enhanced proliferation of ovarian cancer cells [15], (ii) upregulating the oncogenic/growth-promoting transcriptome [16,17], (iii) promoting EMT and invasiveness [18,19], (iv) stimulating the secretion of pro-inflammatory and angiogenic factors (such as TNF-α, IL-6, IL-8, VEGF, etc.) [20,21], and (v) promoting therapy resistance either by supporting an immunosuppressive phenotype or by protecting tumor cells from apoptosis [21].…”
Section: Introductionmentioning
confidence: 99%
“…The pleiotropic protein p62/ SQSTM1 is subjected to degradation during autophagy, and its expression has been demonstrated to increase in primary HNSCC tumors. CYCS encodes the core component protein of the mitochondrial electron transport chain, which is also involved in the initiation of apoptosis and various tumor processes (40,41). Although the mechanisms of some of these genes in HNSCC were not clear in the present study, studies have also confirmed that they could be involved in the occurrence and development of tumors in other cancers.…”
Section: Discussionmentioning
confidence: 51%